الفتاوى عبر الفضائيات - Marzouqi, H.M.A.; Hammad H.K.A.M. (Universiti Sains Islam Malaysia, 2024)
This paper addresses the subject of fatwa via satellite channels, seeking to achieve a set of objectives; which are: analysis of the nature of fatwa via satellite channels, demonstration of fatwa via satellite channels positives, showing the negative effects of fatwa via satellite channels, and providing controls and proposed solutions. The study follows a descriptive analytical method and concludes that the fatwa is an answer to a religion-related question. Furthermore, fatwa programs via satellite channels appear mostly on two types; first, pre-recorded fatwa programs and second, live fatwa programs. The two researchers demonstrate the most prominent fatwa pros via satellite channels; including: clarifying the sharia law of what people face in their life, the dissemination of jurisprudence culture, as well as the dissemination of schools of fiqh culture and presenting other schools of fiqh views, and the convergence among schools of fiqh. The researchers point that negative effects of fatwa via satellite channels are: the dissemination of anomalies and abandoned fiqh views, the weakening of doctrinal unity in communities, in addition to causing chaos and confusion among Muslims, the prevailing of spirit of trading for some channels, the proliferation of anomalies fatwa that need to be reviewed, and the failure to observe the conditions of each country and the circumstances of each community. The study concludes by presenting some controls and proposed solutions, including: avoiding capriciousness in fatwa, avoid tracking sharia permits, anomalies, and narrations that comes from outweighing one report over other, in addition to avoid leniency in fatwa. The researchers assert the need for a fatwa committee or an official center of fatwa in Muslim countries, choose the qualified for Issuing fatwa via satellite channels, and restricting fatwa to them; in addition to organizing fatwa through the development of multiple mechanisms, including allocating mufti to a kind of issues, the requirement of shura in general fatwa, and determine fatwa approach and controls, with the interest of increasing space of time allotted for live fatwa programs in satellite channels to be enough to answer the questions posed. Moreover, the good preparing of muftis, holding regular meetings for those who are in the position of Ifta to review and clarify what is emerging of scholar duties and religious scientific institutions in order to reduce prejudice in fatwa.